First report of Pseudotelorchis yacarei catto & amato, 1993 (Telorchiidae) in Caiman latirostris (daudin, 1802) (Alligatoridae) in Brazil - Rondon Werneck, Max (2023)
Caiman latirostris (Daudin, 1802) occurs in South America, where its geographic distribution extends down to Uruguay. Very little is known about helminths in C. latirostris; therefore, the present study reports the first occurrence of Pseudotelorchis yacarei Catto & Amato, 1993 in these animals. Six young and juvenile specimens of C. Latirostris were collected in Caravelas, Bahia, Brazil. The animals were necropsied and six animals had their digestive tracts evaluated for further analysis. In 5 of the 6 hosts analyzed, 16 specimens of P. yacarei were collected from the stomach and small intestine, thus with a prevalence of 83%. Hence, this study presents the broad-snouted caiman as a new host of P. yacarei.